Buoyancy-driven nanomaterial viscoplastic flow configured by magnetized stretchy regime in frames of varying thermo-solutal properties: Cattaneo-christov formulation - M. Ijaz Khan (Case Studies in Thermal Engineering)
Nanomaterials have achieved considerable importance for their astonishing heat transference aptitudes and distinct utilizations across energy storage, biomedical technologies, solar systems, electronic cooling and nuclear reactors. Comprehending their heat transportation performance is essential for strengthening their execution across these industries. In this research, a steady-state viscoplastic model subject to generalized fluxes which includes thermosolutal relaxation time characteristics is formulated. Buoyancy-driven convective flow induced by stretchable convective surface is under consideration. Transport expressions are subject to Brownian diffusion, improved Fourier relation, thermophoresis, varying conductivity, chemical reaction, improved Fickian relation and varying diffusivity. Apposite variables are deployed for non-dimensionalization. The obtained non-dimensionalized mathematical model is analytically tackled through homotopic series solution approach. The graphical analysis of dimensionless distributions (that is concentration, velocity, skin-friction and temperature) for sundry physical factors is elaborated. The analytically computed outcomes are compared with existing schemes and a reasonable agreement is found. Besides, it is investigated that escalating material factor yields lower velocity.